Association between public knowledge regarding antibiotics and self-medication with antibiotics in Teling Atas Community Health Center, East Indonesia (Medical Journal of Indonesia, 2017)
Background: Self-medication with antibiotics increases the risk of resistance, which leads to higher morbidity and mortality. The community plays an important role in preventing and controlling the spread of antibiotic resistance. This study aims to determine factors associated with antibiotics self-medication practices in the community, which are the key to developing effective intervention programs. Methods: This cross-sectional study was conducted between September and October 2015 at Teling Atas Community Health Center in Wanea, a sub-district of East Indonesia region. Data was collected by a questionnaire-guided interview. There were 35 questions which cover respondent demographics, antibiotic use, and respondents’ knowledge about antibiotics. Logistic regression was used to analyze the association between self-medication with antibiotics and respondents’ level of knowledge as well as other factors. Results: Among 400 respondents, there were 240 (60%) who had used antibiotics within 6 months prior to the interview and 180 (45.0%) who had self-medicated. Wounds or skin diseases (32.2%) were main reasons for self-medication. The majority of respondents self-medicated on their own initiatives (70.6%) and purchased antibiotics in pharmacies (52.2%). The mean score for respondent knowledge about antibiotic was categorized as “moderate” (score 7.14±2.49). Respondents with lower knowledge scores had higher probabilities to self-medicate with antibiotics than those with higher scores (OR= 16.86; 95% CI= 4.25–66.83). Conclusion: Self-medication practices with antibiotics in this study are associated with age, family income, and knowledge. Since poorer knowledge about antibiotics is associated with a higher probability of self-medication with antibiotics, education programs to improve public awareness are needed.